Hubungan Antara Dukungan Sosial Teman Sebaya Terhadap Resiliensi Akademik Siswa Kelas X di SMA Negeri 1 Mertoyudan - Nadiya Permatasari; Deni Santi Pertiwi Pertiwi (LPPM Universitas Proklamasi 45, 2025)
Peer social support plays an important role in improving the academic resilience of grade X students at SMA Negeri 1 Mertoyudan. This support helps individuals cope with academic stress, increases self-confidence, and improves their ability to face challenges. With good social support, students tend to be better able to recover from difficulties and achieve better academic performance. The purpose of this study was to determine the relationship between peer social support and academic resilience of grade X students at SMA Negeri 1 Mertoyudan. The method in this study used a quantitative method with a correlational approach. The data collection tool used a peer social support scale based on aspects of Sarafino and Smith (2011) which was modified from the research of Ningsih and Astuti (2024) and an academic resilience scale based on aspects of Cassidy (2016) which was modified from the research of Afriyeni and Rahayunings. The sampling technique used purposive sampling. The subjects in this study were grade X high school students aged 15-18 years. The data analysis technique used in the hypothesis test used Pearson Product Moment. So that the results of the hypothesis test were obtained with a correlation value index of 0.393 with a significance level of 0.000 (p <0.01), so that the results of this study indicate that there is a positive relationship which means that the higher the level of peer social support received, the higher the level of academic resilience in high school students in grade X, conversely, the lower the peer social support, the lower the academic resilience of high school students in grade X.